Feminismo e Emancipação Feminina: Um estudo sobre a concepção da emancipação da mulher negra na Bamidelê– Organização de Mulheres Negras da Paraíba. - Barbosa, Karla Maria da Silva (2016)
As the historical process started to promote the different waves of feminism, other aspects also emerged based on the need for representation of a multiplicity of identities that began to be defended within the feminist movement. Black women who did not feel represented by traditional feminism, make up their own mobilization space, black feminism. Including in this movement the topic of racism, beyond sexism and class issue. This paper focuses on the emancipation of black women, we will develop the research in order to understand and critically analyze the conception of women's emancipation and the role of the black feminism for the emancipation of black women. The research will be conducted with the Bamidele organization - Black Women's Organization of Paraiba, carrying out the characterization of the organization, the profiles of members and women participating in the projects carried out by Bamidele, in order to analyze how the organization understands and carry out the emancipation of black women.